1983
DOI: 10.1002/art.1780260701
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of fibrositis

Abstract: Twenty-two patients with fibrositis, selected from a general medical outpatient population by a screening questionnaire and subsequent evaluation, were compared with age-, sex-, and clinic-matched patients without fibrositis. Although there was a high prevalence of musculoskeletal complaints in both groups, the fibrositis patients had a uniform constellation of symptoms, including axial pain, severe aching and stiffness, morning 'fatigue, and modulation by specific factors. They also had a higher incidence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
3

Year Published

1987
1987
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(12 citation statements)
references
References 21 publications
1
8
0
3
Order By: Relevance
“…Our results suggest that features associated with the tender point count in the general population are similar to those described in patients with fibromyalgia attending hospital 14. Counts were higher in women and in subjects who reported pain, especially those with chronic widespread pain.…”
Section: Discussionsupporting
confidence: 75%
“…Our results suggest that features associated with the tender point count in the general population are similar to those described in patients with fibromyalgia attending hospital 14. Counts were higher in women and in subjects who reported pain, especially those with chronic widespread pain.…”
Section: Discussionsupporting
confidence: 75%
“…Measurement of pain threshold, defined as 'the first barely perceptible pain to appear in an instructed subject under given conditions of noxious stimulation' (1), has been considered an important variable, and elicited by a variety of mechanical (2,3), thermal (4,5,6), vascular (7), chemical (8), and electrical methods (for reviews see 9,10). Pain threshold studies have been performed in normal subjects (9,10,11), and in patients with osteoarthritis of the hip (12), rheumatoid arthritis and ankylosing spondylitis (13), and fibrositis (14,15). To our knowledge only one major study has been reported on the reliability of the pressure algometer as a measure of 'trigger-point' sensitivity in fibrositis (15).…”
Section: Introductionmentioning
confidence: 97%
“…other diagnoses should be entertained. 9 An anecdotally important aspect is that these patients usually want to get better and continue to work in spite of seemtngly excruciating discomfort. This point helps distinguish fibromyalgia patients from ( 1) persons in search of secondary gain and (2) persons with other chronic pain syndromes, such as psychogenic rheumatism, whose physical complaints help them cope with their environment.…”
Section: Monarticular Disordersmentioning
confidence: 99%